Stroke Severity and Outcomes in Patients With Newly Diagnosed Atrial Fibrillation - Watanabe, Kotaro; Okazaki, Shuhei; Kitano, Takaya; Sugiyama, Shintaro; Ohara, Mariko; Kanki, Hideaki; Sasaki, Tsutomu; Sakaguchi, Manabu; Mochizuki, Hideki; Todo, Kenichi (Frontiers in Neurology, 2021)
Background and Purpose: Once a stroke occurs in a patient with atrial fibrillation (AF), it is likely to be severe. Patients with newly diagnosed AF after stroke and those with known AF before stroke have different background characteristics, yet the difference in stroke severity has not been sufficiently evaluated. In the current study, we compared the stroke severity and in-hospital outcomes between these patient groups. Methods: We retrospectively analyzed a database of 196 patients with acute ischemic stroke and AF between January 2010 and October 2019. We divided the patients into two groups: patients with “newly diagnosed AF” and those with “known AF”. We assessed the stroke severity using the National Institute of Health Stroke Scale (NIHSS) score on admission and in-hospital outcomes using the modified Rankin Scale (mRS) score at discharge. Results: The proportion of newly diagnosed AF was 33% (64/196). There were no differences in age, hypertension, diabetes mellitus, and past history of heart failure, between patients with newly diagnosed AF and those with known AF. Patients with newly diagnosed AF were associated with a lower proportion of male sex, a lower proportion of past history of stroke, a lower CHA2DS2-VASc score, and a lower proportion of pre-stroke oral anticoagulation. There were no differences in the NIHSS score on admission (12 [4–19] vs. 9 [3–19]) or the mRS score at discharge (3 [1–5] vs. 3 [1–5]). After adjustment for relevant covariates, newly diagnosed AF was not associated with the NIHSS score on admission (adjusted common odds ratio [OR], 0.85; 95% confidence interval[CI], 0.45–1.60) or the mRS score at discharge (adjusted common OR, 1.67; 95% CI, 0.88–3.18). After propensity score matching, newly diagnosed AF was not associated with the NIHSS score on admission (adjusted common OR, 0.91; 95% CI, 0.48–1.73) and the mRS score at discharge (adjusted common OR, 1.77; 95% CI, 0.92–3.43). Conclusion: Stroke severity and in-hospital outcomes in patients with newly diagnosed AF did not differ from those in patients with known AF after adjustment for clinically relevant factors. The importance of detection of latent AF and subsequent anticoagulation in preventing severe stroke should be further emphasized.